In situ K-edge X-ray absorption spectroscopy of the ligand environment of single-site Au/C catalysts during acetylene hydrochlorination. Issue 27 (29th June 2020) - Malta, Grazia; Kondrat, Simon A.; Freakley, Simon J.; Morgan, David J.; Gibson, Emma K.; Wells, Peter P.; Aramini, Matteo; Gianolio, Diego; Thompson, Paul B. J.; Johnston, Peter; Hutchings, Graham J.
Abstract : In situ chlorine and sulphur XAS shows a dynamic ligand environment around cationic Au single-sites during acetylene hydrochlorination. Abstract : The replacement of HgCl2 /C with Au/C as a catalyst for acetylene hydrochlorination represents a significant reduction in the environmental impact of this industrial process. Under reaction conditions atomically dispersed cationic Au species are the catalytic active site, representing a large-scale application of heterogeneous single-site catalysts. While the metal nuclearity and oxidation state under operating conditions has been investigated in catalysts prepared from aqua regia and thiosulphate, limited studies have focused on the ligand environment surrounding the metal centre. We now report K-edge soft X-ray absorption spectroscopy of the Cl and S ligand species used to stabilise these isolated cationic Au centres in the harsh reaction conditions. We demonstrate the presence of three distinct Cl species in the materials; inorganic Cl −, Au–Cl, and C–Cl and how these species evolve during reaction. Direct evidence of Au–S interactions is confirmed in catalysts prepared using thiosulfate precursors which show high stability towards reduction to inactive metal nanoparticles. This stability was clear during gas switching experiments, where exposure to C2 H2 alone did not dramatically alter the Au electronic structure and consequently did not deactivate the thiosulfate catalyst.